Nanoscale aggregation of doxorubicin-short peptide conjugates for enzyme-responsive delivery with various MOF carriers: In-silico steps towards smart cancer chemotherapy. (May 2022) - Dahri, Mohammad; Abolmaali, Samira Sadat; Maleki, Reza; Najafi, Haniyeh; Abedanzadeh, Mozhgan; Tamaddon, Ali Mohammad
Abstract: Drug conjugation with enzyme-sensitive peptides is one of the innovative smart delivery systems for cancer therapy. This delivery method has some advantages, such as lowering side effects and increasing treatment selectivity. Herein, two conjugates of doxorubicin and small peptide are designed that are sensitive to Cathepsin B, a tumor homing enzyme. The formation of nanoparticles at three different numbers of drug peptide prodrugs (including 30, 50, and 70 prodrugs) was studied. In addition, three metal-organic frameworks (MOF) nanocarriers, including Zeolitic Imidazolate Frameworks (ZIF), Universitetet I Oslo MOF (UIO-66), and MOF of Hong Kong University of Science and Technology (HKUST-1), were used to increase the resistance of the prodrugs to decomposition during blood flow circulation. Then, the interactions between doxorubicin's prodrug and different MOFs were investigated. Furthermore, the impact of microfluidics on nanoparticle interactions was studied. Molecular dynamic simulation was used to investigate thermodynamic and conformational parameters. The results showed that the concentration of doxorubicin prodrugs affected cluster formation. Moreover, based on Gibb's free energy analysis, the interaction of these prodrugs with various types of MOFs revealed more spontaneous interactions in microfluidic modeling conditions. ZIF had the best and most stable interactions with the prodrugs in bulk and microfluidic modeling. As a result, the best and most stable state was associated with a lower concentration of these prodrugs with ZIF in the microfluidic condition. Graphical abstract: Image 1 Highlights: At the lowest concentration, appropriate particle formation of carrier-free peptide-drug conjugates occurred. Peptide-drug conjugates interacted the best with ZIF nanocarriers. In the microfluidic environment, interference was more appropriate for prodrug loading.